The Impact of Communication Skills Training Programs on Improving Work Relationships in the Office Environment - Thalib, Najdah; Khan, Omar; Aziz, Safiullah (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2025)
Effective communication skills are essential for fostering positive work relationships and enhancing collaboration in office environments. However, many employees struggle with communication barriers that hinder their ability to work effectively with colleagues, leading to misunderstandings and reduced productivity. Communication skills training programs have been proposed as a solution to improve interpersonal communication, but their impact on work relationships in the office environment remains underexplored. This study aims to evaluate the effectiveness of communication skills training programs in improving work relationships among employees in office settings. The research employed a pre- and post-intervention survey design, involving 150 employees from various departments in a corporate office. Participants completed assessments on their communication effectiveness and work relationship quality before and after undergoing a 6-week communication training program. The results demonstrated significant improvements in employees’ ability to express themselves clearly, listen actively, and resolve conflicts, which in turn enhanced the quality of their work relationships. Participants reported increased trust, cooperation, and mutual respect in their interactions with colleagues. The study concludes that communication skills training programs can effectively improve interpersonal relationships in the office, leading to a more harmonious and productive work environment.